The Hannover Coupler V2: Audiological outcomes of a round window coupler for the Vibrant Soundbridge. Issue 3 (28th May 2022) - Knölke, Nicole; Murawski, Dawid; Wardenga, Nina; Busch, Susan; Maier, Hannes; Lenarz, Thomas
Abstract: Introduction: The Hannover Coupler version 2 (HC2) was designed to (1) adapt the coupler geometry to the round window (RW) niche (2) to stabilize the floating mass transducer, and (3) to control static coupling forces to the RW. First audiological outcomes with a custom‐made HC2 are reported here. Material and Methods: Ten patients were enrolled in our site‐initiated, prospective study. To assess audiological outcomes up to 6 months, preoperative and postoperative hearing thresholds, word recognition score (WRS) at 65 dB SPL and the speech recognition threshold in quiet and noise were performed. The effective gain (EG) and the coupling efficiency were calculated. Results: One revision surgery had to be performed during the study period and a significant, but clinically not relevant bone conduction thresholds change was observed at 4 and 6 kHz at 6‐month follow‐up. At 6 months, the median WRS ( n  = 10) improved significantly from 0% to 80%. The median speech reception threshold in noise improved significantly from 11.6 to −2.4 dB SNR, and in quiet significantly from 79.6 to 44.4 dB SPL. The average EG of −1.3 dB indicated a closure of the air bone gap. The determined average coupling efficiency of 23.3 dB was within the acceptance range suggested by the manufacturer. Conclusion: For patients with mixed hearing loss and multiple ear surgeries, the HC2 provided good and stable speech recognition results exceeding published results of RW coupling without a coupler or coupling with the RW soft coupler. Abstract :